Upaya Mengurangi Cacat Produk Tembaga pada Proses Produksi Pt. XYZ dengan Pendekatan Metode Six Sigma dan Analisa 5W+1H - Eka Haris Setyawan; Akhmad Wasiur Rizqi (Science and Physics Education Journal (SPEJ), 2025)
Abstract: This study aims to minimize product defects in the copper production process at PT. XYZ. The Six Sigma method was used with the 5W+1H analysis approach. The data analysis results show that from the Refinery Plant production during May–June 2025, with a total of 1,249,320 units, 1,903 units were defective, or 15%. The main types of defects include Nodular Copper (31%), Thin Cathodes (22%), Moldy Cathodes (11%), Bent Cathodes (10%), and Broken Edge Strips (6%). In conclusion, through the DMAIC process, the causes of defects were analyzed using Pareto diagrams, fishbone diagrams, and RCA. The results showed that human, machine, material, method, and environmental factors contributed to product defects. Recommendations for improvement include operator training, routine machine maintenance, material control, and improving work environment conditions. The implementation of this method is expected to reduce the defect rate, improve product quality, and support the company's competitiveness.   Keywords: DMAIC, Quality, Defective Products, Six Sigma, 5W+1H